To Study The Prevalence Of Greater Trochanteric Pain Syndrome In Gym Going Obese Women - Dhamanekar, Richa Abhijeet; Sagar, Javid H (Journal of Neonatal Surgery, 2025)
background: greater trochanteric pain syndrome (gtps) is a common cause of hip pain characterized by discomfort around greater trochanter. obesity is a risk factor for musculoskeletal disorder, and the combination of excess body weight and physical activity may exacerbate the likelihood of developing greater trochanteric pain syndrome. methods: a total of 102 obese women who regularly attended gyms participated in this cross-sectional study. gtps was diagnosed based on clinical tests, including the resisted hip abduction test, jump sign, and single leg stance test. results: the prevalence of gtps among the participants was found to be 22.55%. a significant number of individuals presented with positive clinical signs, indicating a notable association between obesity and gtps in gym-going women. conclusion: greater trochanteric pain syndrome is prevalent in obese women engaged in gym activities, highlighting the need for targeted interventions to prevent and manage hip pain in this population. strength training, weight management, and rehabilitation strategies should be incorporated to reduce the risk and impact of gtps.